Combination Therapies for the Treatment of Advanced Melanoma: A Review of Current Evidence. (12th February 2014) - Voskoboynik, Mark; Arkenau, Hendrik-Tobias
Abstract : The treatment of advanced melanoma has been revolutionised in recent years with the advent of a range of new therapies. BRAF inhibitors, such as vemurafenib, have demonstrated improvements in the overall survival of patients with advanced melanoma that harbour a BRAF V600 mutation. Alongside these targeted therapies, novel immune-checkpoint inhibitors, such as ipilimumab, have also been developed and have produced similarly improved outcomes for patients. For the first time in the history of melanoma, monotherapy with each of these drugs has produced improvements in the overall survival of patients with advanced disease. Building on this initial success, there has been intense interest in developing combination therapies predominantly with either dual blockade of the MAPK oncogenic pathway or dual immune-checkpoint blockade. The current evidence for the use of these combination therapies will be presented here.